O grau de heterogeneidade da estrutura agrícola da Regi\~ao Centro-Oeste segundo os Censos Agropecuários 1995, 2006 e 2017 - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– It is in the middle of the transformation process of agricultural structures that the central question of this investigation arises, that is, how is the degree of heterogeneity of work, in the context of the agricultural structure of the federation units, in the Midwest region according to the agricultural censuses of 1995, 2006 and 2017? The central idea of this question is to test and validate, empirically, the theoretical evidence pointed out by the Economic Commission for Latin America and the Caribbean (Eclac) in what refers to the productive structures of peripheral economies such as the Brazilian one, which are marked by a strong heterogeneity productive. The structural historical method is adopted, which aims to decompose, classify, organize, systematize and interpret the information contained in the databases of the Ministry of Economy's Foreign Trade Secretariat (Secex) and in the data from the 1995, 2006 and Agricultural Censuses 2017 of the Brazilian Institute of Geography and Statistics (IBGE). Finally, it is noted that this advance in the productivity of agricultural work among the units of the federation has further deepened the degree of heterogeneity that exists between modernized economies and those still tied to the fetters of traditional agriculture and subsistence. In the particular case of the Midwest, Mato Grosso was the state that most increased its labor productivity in agriculture, followed by Mato Grosso do Sul, Goiás and, finally, the Federal District. However, it is important to note that the degree of heterogeneity of the municipal agricultural structure in the states of the Midwest showed a pattern between the census years. In general, between the 1995, 2006 and 2017 census years, the degree of heterogeneity in the agricultural structure of the state of Goiás was greater vis-à-vis the other states, at the same time that the state of Mato Grosso do Sul presented a greater degree of homogeneity in its productive structure, given the regional context.
Keywords: R12; 330; structural heterogeneity; labor productivity; Midwest